Social Commerce Adoption: A Consumer’s Perspective to an Emergent Frontier - Savanid Vatanasakdakul (20185785) (2023)
The mass diffusion of social media has enabled new commercial models in retailing. It heralded the emergence of social commerce, with consumers and retailers interacting and transacting through a multitude of social media. While the organizational benefits of such interactions have attracted much attention, little is known about the consumers’ motives. In addressing this limitation, a theoretical model was developed, extending the UTAUT2 framework. The model was then operationalized, and quantitative data collected from 108 Indonesian consumers engaged in social commerce and analyzed using the partial least squares method. The findings point to new dynamics influencing consumer behavior, driven by lifestyle, price value, facilitating conditions, and pragmatisms. Interestingly, social influence was significant yet negative indicating that consumers may be developing a distinct online persona, which is more independent and assertive to normative pressures. The results hold important theoretical and practical implications for the rapidly emerging field of social commerce. Other Information Published in: Human Behavior and Emerging Technologies License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1155/2023/3239491